Shattered hips, unbreakable spirit: navigating HIV therapy's roadblocks - Kwan, Li Li; Zainulabid, Ummu Afeera; Hussin, Fara Rahidah; Cheong, Xiong Khee; Periyasamy, Petrick (Federation of Islamic Medical Associations (FIMA), 2023)
Protease inhibitors (PIs) have revolutionized HIV treatment; however, their long-term use can have unforeseen consequences. We unravel the captivating case of a man with retroviral disease, where the saga of bilateral hip avascular necrosis (AVN) unfolded due to prolonged exposure to these medications. A 39-year-old man with HIV and Hepatitis B co-infection, on first line antiretroviral therapy (ART) regimen consisting Tenofovir Disoproxil Fumarate/Emtricitabine (TDF/FTC) and Efavirenz (EFV). He experienced virological failure due to non-compliance to the medications, and subsequently switched to a second-line ART, which is Lopinavir/Ritonavir (LPV/r) with TDF/FTC. He is then able to achieve viral load suppression. Patient experienced progressively worsening bilateral hip pain three years after initiation of second line ART and relied on crutches for mobility. Physical examination revealed an antalgic gait and motion limitation in both hips. Hip radiography and scanograms confirmed bilateral hip AVN. A diagnosis of PI induced AVN was established after ruled out alternative causes. His mobility was restored with bilateral hip replacement. ART regimen was revised by switching LPV/r to a new antiviral agent - Dolutegravir (DTG). Patient remains well and virologically suppressed. The captivating journey of the patient, whose life was interrupted by the ravages of bilateral hip AVN, led us to a conclusion. The limitations of the available ART options play a significant role in shaping the patient’s path. Although the patient experienced hip pain, the search for a suitable ART regimen became a race against time. The anticipation of a breakthrough was palpable, as the impending arrival of DTG promised a new era of therapeutic possibilities.